2003
DOI: 10.1021/cm030057v
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Reactivity Mechanism of M3B2O6 (with M = Co, Ni, and Cu) toward Lithium

Abstract: The electrochemical reactivity mechanism of M 3 B 2 O 6 (with M ) Co, Ni, and Cu) powders toward lithium was studied by a combination of transmission electron microscopy (TEM), infrared spectroscopy (IR), 11 B magic angle spinning nuclear magnetic resonance (MAS NMR), and electrochemical techniques. The electrochemical properties of these materials as anodes for lithium batteries were investigated and found to be similar to those of 3d-metal oxides. In fact, the reduction process of 3d-metal borates involves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Although the initial discharge capacities are close to 1000 mAh g − 1 , their response upon cycling is rather poor, with the best values (350 mAh g − 1 after 35 cycles) being reported for Fe 3 BO 6 . [ 283 ] In this case, the integrity of the borate unit upon complete reduction has been proved in the case of Cu 3 B 2 O 6 , [ 288 ] but formation of Li 3 BO 3 was shown to be concomitant to a decomposition into Li 2 O and metallic nanoparticles, which are the only active components in further cycling.…”
Section: Progress Reportmentioning
confidence: 82%
See 1 more Smart Citation
“…Although the initial discharge capacities are close to 1000 mAh g − 1 , their response upon cycling is rather poor, with the best values (350 mAh g − 1 after 35 cycles) being reported for Fe 3 BO 6 . [ 283 ] In this case, the integrity of the borate unit upon complete reduction has been proved in the case of Cu 3 B 2 O 6 , [ 288 ] but formation of Li 3 BO 3 was shown to be concomitant to a decomposition into Li 2 O and metallic nanoparticles, which are the only active components in further cycling.…”
Section: Progress Reportmentioning
confidence: 82%
“…Finally, a few studies have been devoted to the reactivity of borates such as MBO 3 (M = V and Fe [283][284][285] ), M 3 BO 6 (M = Fe [ 283 , 286 ] and Cr [ 287 ] ), and M 3 B 2 O 6 (M = Co, Ni, and Cu) [ 288 ] as negative electrodes. Although the initial discharge capacities are close to 1000 mAh g − 1 , their response upon cycling is rather poor, with the best values (350 mAh g − 1 after 35 cycles) being reported for Fe 3 BO 6 .…”
Section: Progress Reportmentioning
confidence: 99%
“…For these phases, a conversion reaction mechanism during lithiation was confirmed by Débart et al 7 Based on their work, a conversion reaction mechanism was also postulated for Cu 3 B 2 O 6 . In situ X-ray patterns in Ref.…”
mentioning
confidence: 75%
“…Stoichiometric amounts of CuO copper oxide and boric acid H 3 BO 3 were mixed, pressed into pellets, and put into a furnace at 900 C. After 24 h, the material was reground, pressed into pellets and heated for additional 24 h. The obtained green powder was characterized by XRD which confirmed the purity of the Cu 3 B 2 O 6 phase. 6 This phase crystallizes in a triclinic structure with a ¼ 3.3620(3) Å , b ¼ 19.681(2) Å , c ¼ 19.673(2) Å , a ¼ 88.821 (6) , b ¼ 69.703 (6) , c ¼ 70.063 (7) . The particles size of the active material affects the capacity stability during cycling.…”
Section: Methodsmentioning
confidence: 99%
“…It was later on demonstrated that this new Li reactivity mechanism was not specific to oxides but could also be 4 found with sulphides, nitrides, fluorides, and phosphides. [6][7][8][9] As compared to the classical insertion reactions that govern the energy stocked in the actual Li-ion batteries, and which are limited to 1e -even 0.5e -per 3d metal atom (LiCoO 2 ), these new conversion reactions that can involve 2e -, or more, (per 3d metal atom), were thought of as a new means to enable the creation of a new class of electrodes with staggering capacity gains over various voltage ranges depending on the nature of the X anion.…”
mentioning
confidence: 99%